De novo Sequencing and Comparative Transcriptome Analyses Provide First Insights Into Polysaccharide Biosynthesis During Fruiting Body Development of Lentinula edodes - Li, Qiaozhen; Chen, Jing; Liu, Jianyu; Yu, Hailong; Zhang, Lujun; Song, Chunyan; Li, Yu; Jiang, Ning; Tan, Qi; Shang, Xiaodong; Gu, Yunfu (Frontiers in Microbiology, 2021)
As the first step toward understanding the polysaccharides biosynthesis in L.edodes fruiting bodies, we selected fruiting bodies at four developmental stages with significant differences in polysaccharide yields, then performed de novo sequencing and comparative transcriptomic analysis by using high-throughput Illumina RNA-sequencing. KS1P30, KS2P30, KS3P30, KS4P30 were obtained from four developmental stages respectively by hot water extract and 30% ethanol precipitation. These four polysaccharides had good immune activity in vitro, all of which were β-glucopyranose with high molecular weight. Glucose was the main monosaccharide component of these polysaccharides. High-quality clean reads (57.88, 53.17, 53.28, and 47.56 million for different growth stages) and mapping ratios ranged from 84.75% to 90.11% were obtained. In total, 11493 (96.56%) unigenes and 18924(97.46%) transcripts were successfully annotated in five public data bases. Important findings based on quantitative developmental transcriptome analysis and its predictions are as follows: (i) The β-1,3-glucan biosynthetic pathway was elucidated in L.edodes fruiting bodies. (ii) Synthesis and decomposition processes of β-1,3-glucan were predicted in L.edodes fruiting bodies different development stages. (iii) Six genes (ugp, gls1, gls2, glg, pgm, pgi) for key enzymes were proposed for β-1,3-glucan overproduction in L.edodes fruiting bodies. This study offers a new idea for the polysaccharide biosynthesis of L.edodes friuting bodies, and candidate genes can be used as important resources for biotechnology and molecular breeding to regulate L.edodes friuting bodies polysaccharide biosynthesis.